A significant seawater sulfate reservoir at 2.0 Ga determined from multiple sulfur isotope analyses of the Paleoproterozoic Degrussa Cu-Au volcanogenic massive sulfide deposit, Western Australia. (15th February 2021) - LaFlamme, Crystal; Barré, Guillaume; Fiorentini, Marco L.; Beaudoin, Georges; Occhipinti, Sandra; Bell, Joshua
Abstract: The Proterozoic rock record displays secular change from ferruginous to an oxic hydrosphere over the course of 2 billion years; however, debate continues on the periodicity, rate of change and steps in following atmospheric oxygenation that ultimately led to an oxygenated ocean. This is partly due to poor preservation of the Paleoproterozoic marine sedimentary record in the few hundred million years after the Great Oxidation Event. Whereas the 2.0 Ga rock record preserves only rare chemical sediments, it contains significant mafic igneous provinces, which are known to locally host volcanogenic massive sulfide (VMS) deposits. These hydrothermal environments fossilize the ancient interaction at the seafloor interface between volcanic rocks and seawater. In this context, the 2.01 Ga Degrussa VMS deposit of the Paleoproterozoic Capricorn Orogen, Western Australia offers an opportunity to probe the ancient ocean composition. The Degrussa VMS deposit preserves massive sulfide mineralisation (pyrite – chalcopyrite – pyrrhotite ± sphalerite ± galena) hosted in turbiditic sedimentary rocks interlayered with basaltic flows and cut by numerous gabbroic sills. Exhalite layers are composed of hematite and jasper associated with magnetite. This study documents the multiple sulfur isotope composition of the Degrussa VMS deposit through an integrated analytical approach, which comprises bulk fluorination gas chromatography isotope ratio mass spectrometry and in situ secondary ion mass spectrometry. By comparing the ultra-high precision bulk measurements ( n  = 21) with in situ measurements of variably-textured grains of pyrite, chalcopyrite and pyrrhotite ( n  = 252), we determine that VMS mineralisation yields δ 34 S between +2‰ and +5‰ with a peak at ∼+2.9‰, and negative Δ 33 S signal ranging from −0.08 to 0.00‰. A two component δ 34 S-Δ 33 S mixing model indicates 11% of H2 S derived from thermochemically reduced seawater sulfate mixed with magmatic H2 S. The most negative Δ 33 S values must be explained by interaction with sulfate in the near-surface, undergoing complex dissolution-reprecipitation reactions, necessitating a minimum seawater sulfate reservoir of ∼2 mmol/L, or 7% modern seawater at 2.01 Ga.